Meta Analisis Efektivitas Penggunaan Model Value Clarification Technique (VCT) terhadap Hasil Belajar PKn Siswa Sekolah Dasar - Ni Putu Candra Prastya Dewi (STAHN Mpu Kuturan Singaraja, 2023)
The aims of this study were 1) to find out the differences in students' Civics learning outcomes before using the Model Value Clarification Technique (VCT) and after using the Model Value Clarification Technique (VCT). 2) To determine the level of effectiveness of using the Model Value Clarification Technique (VCT) in improving Civics learning outcomes. This type of research is a meta-analytic research with a quantitative approach. Data collection by browsing e-journals using Google Scholar. Based on the search results, from 2,680 articles, 20 articles were selected that met the criteria for further analysis. Data analysis begins by calculating the N-Gain Score and the percentage of the N-Gain Score (%). After that, the hypothesis was tested using the Paired Samples T Test with the help of SPSS 26. The results showed that there were significant differences in the learning outcomes of Civics students before using the Model Value Clarification Technique (VCT) and after using the Model Value Clarification Technique (VCT). Learning using the Model Value Clarification Technique (VCT) is quite effective in improving Civics learning outcomes.